Perlindungan Hukum atas Pembatasan Pekerja Outsourcing dalam Undang-Undang Cipta Kerja Tahun 2023 - Azzahra, Diazterra; Pande Yogantara S (Ethics and Law Journal: Business and Notary, 2026)
The aspect of employment is related to the application of human rights law through legal protection guarantees. Labor from the community selected for its qualifications must be given a guarantee of welfare, especially in the outsourcing system. However, after the enactment of the Job Creation Law, outsourced workers are faced with labor regulations that limit their ability to work, causing legal uncertainty for workers. This study was carried out using the normative legal research method, by means of which laws and regulations are studied to be conceptualized concretely from legal science literature. The results of this study show that Article 64 of the previous Labor Law regulates Indonesian legal arrangements regarding restrictions on outsourcing. This contained requirements for outsourcing, such as the nature of the work being handed over, the legal entity involved, a written agreement, and employment protection. Currently, the outsourcing restrictions amended in the Job Creation Law have been removed, and replaced with the concept of PKWT or PKWTT in Government Regulation Number 35 of 2021. Keywords: Legal Protection, Outsourcing, Worker Restrictions